ULK4 in Neurodevelopmental and Neuropsychiatric Disorders - Luo, Shilin; Zheng, Nanxi; Lang, Bing (Frontiers in Cell and Developmental Biology, 2022)
The gene Unc51-like kinase 4 (ULK4) belongs to the Unc-51-like serine/threonine kinase family and is assumed to encode a pseudokinase with unclear function. Recently, emerging evidence has suggested that ULK4 may be etiologically involved in a spectrum of neuropsychiatric disorders including schizophrenia, but the underlying mechanism remains unaddressed. Here, we summarize the key findings of the structure and function of ULK4 protein to provide comprehensive insights to better understand ULK4-related neurodevelopmental and neuropsychiatric disorders and to aid the development of a ULK4-based therapeutic strategy.